Penguatan pengetahuan guru Biologi dalam penanganan kutu kepala (Pediculus humanus capitis) - Adrianto, Hebert; Tanzilia, May Fanny; Lindarto, Wira Widjaya; Dinata, Yuwono Marta; Goein, Amadeus Michel; Andriani, Nathania Disa Ariesta (Jurnal Pengabdian Masyarakat: Humanity and Medicine, 2021)
Head lice infestation (Pediculus humanus capitis) is an obligate ectoparasite infestation in human hair. The Sidoarjo Biology MGMP has been working with the service team for three years. The interview results were obtained with the management of the Sidoarjo Biology MGMP the need to strengthen knowledge about head lice. This activity aims to improve the understanding of head lice (Pediculus humanus capitis) for biology teachers in the Sidoarjo district. Training activities are carried out online using Zoom. The form of activities in the form of material delivery, questions and answers, and tests. The result of this service is that there is an increase in participants' knowledge from the average value of 62.75 to 84.13. Most of the teachers have come across cases and have given initial action to pediculosis sufferers. In general, the training event went smoothly and received a positive response.